Assessing snowball effect of COVID-19 pandemic on Indian dairy sector - BHANDARI, GUNJAN; LAL, PRIYANKA; CHAUDHARY, UDITA; K, HARITHA; MALHOTRA, R; CHANDEL, B S (The Indian Journal of Animal Sciences, 2022)
Dairy sector experienced supply setback as well as demand uncertainties owing to restrictive measures imposed for the control of COVID-19 pandemic. The present paper attempts to assess the multi-dimensional impact of pandemic on dairying by reviewing the emerging literature. The assessment shows that availability of feed and fodder declined by 11% during the initial months of lockdown making it the most affected supply chain. The dairy farmers incurred dual losses due to increase in cost of milk production (+6%) and simultaneous fall in milk prices (–5.6%). Major challenge for the dairy processors was posed by the fall in demand which declined steeply particularly for the ice-creams and milk based beverages. The estimated loss incurred by the dairy farmers is `4,000 per milch animal in the initial 40 days of lockdown which can further rise if losses due to missed artificial insemination and change in animal prices are also taken into account. Assessment of impact on the unorganized dairy sector is still unavailable without which the loss estimation from the perspective of milk buyers stands incomplete. Huge inventories of the Skimmed Milk Powder (SMP) are the immediate challenge which requires proper policy intervention for arresting further losses in the dairy sector.